Analysis of fuel rod performance per cycle: Temperature field, FGP release, swelling. (1st October 2021) - Lys, Stepan; Kanyuka, Alexander
Highlights: A system of thermophysical criteria is presented by us. These criteria are used to assess the serviceability of fuel rods. Analyzed of experimentally determined data on the in-pile densification of VVER fuel. Based on the analysis the empiric ratio was derived by us. Abstract: Models for calculating gas release, pressure of gases within fuel rod cladding, fuel swelling and thermal conductivity, and fuel-cladding gap conductance are briefly described. The thermophysical condition of fuels in a reactor core is one of the main factors that determine their serviceability. The stress-strained condition of fuel claddings under design operating conditions is closely related to fuel rod temperature, swelling, gas release from fuel pellets and the mode in which they change during the cycle and transients. Aside from this, those parameters are an independent goal of studies since their ultimate values are governed by the system of design criteria. In the group of thermal physics criteria, consideration is given to maximal temperatures of fuel, FGP releases, and pressure of gases within a fuel cladding. It is shown that the micro-processes of fission gas incipience and migration in fuel under irradiation are closely related to essentially all spectrum of macro-characteristics of fuel, namely, temperature field and heat rating, fuel burn-up, pressure and composition of gas within a fuel rod, characteristics of the stress-strained condition of fuel column and cladding. The adequate computer analysis of the dynamics of FG behaviour and affected structure changes in a wide range of irradiation conditions is most important for prediction of fuel rod serviceability and, on the other hand, it may serve to corroborate the adequacy of prediction of fuel rod macro-condition characteristics using the full-scale code.